GAYA BAHASA METAFORA DALAM LIRIK LAGU, ‘’ BERTAUT’’ , KARYA NADIN AMIZAH - Maria Anggraini Devira Bria; Semuel H. Nitbani; Margareta P.E. Djokaho (STKIP Subang, 2026)
This study focuses on the forms and significations of metaphors in the lyrics of the song